Effect of photoperiod on the cellular fatty acid composition of three tropical marine microalgae - Lim, K.C.; Zaleha, K. (Penerbit Universiti Kebangsaan Malaysia, 2013)
The culture of microalgae in hatcheries is promoted for their high essential fatty acid (EFA) content which favors the successful rearing of aquatic animals. In this study, batch cultures of Chaetoceros calcitrans, Chlorella sp. and Nannochloropsis sp.were acclimated under photoperiods of 24:0h, 12:12h and 8:16h L/D regimes at 20ºC to analyze for cellular fatty acid in the logarithmic growth phase. The various photoperiods resulted in differences of cellular fatty acid content of cultivated microalgae revealing influences and strong interactions between the photoperiods studied. The photoperiod of 12:12h L/D regime is recommended for fast and economic batch culture production of Chaetoceros calcitrans, Chlorella sp. and Nannochloropsis sp. cells rich in EFA.